TINJAUAN YURIDIS TINDAK PIDANA PEMERKOSAAN PADA ORANG DENGAN GANGGUAN JIWA DITINJAU DARI HUKUM INDONESIA - Waskito, Sarwo; Purborini, Vivi Sylvia (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
People who have mental disorders have a high risk of becoming victims of rape. Access to legal services for people with mental disorders is still very limited and some people with mental disorders have no legal protection at all. The type of research used in this research is doctrinal (normative) research, also called library research methods. The Law on Protection of Witnesses and Victims cannot be said to be sufficient as a basis for providing human rights as regulated in Article 42 of the Human Rights Law to victims of criminal acts of rape who have the status of people with mental disorders because the regional government carries out limited fulfillment of victims' rights